Eddy‐Induced Dispersion of Sea Ice Floes at the Marginal Ice Zone - Mukund Gupta; Emma Gürcan; Andrew F. Thompson (Geophysical Research Letters)
Abstract Ocean heat exchanges at the marginal ice zone (MIZ) play an important role in melting sea ice. Mixed‐layer eddies transport heat and ice floes across the MIZ, facilitating the pack's access to warm waters. This study explores these frontal dynamics using disk‐shaped floes coupled to an upper‐ocean model simulating the sea ice edge. Numerical experiments reveal that small floes respond more strongly to fine‐scale ocean currents, which favors higher dispersion rates and weakens sea ice drag onto the underlying ocean. Floes with radii smaller than resolved turbulent filaments (∼2–4 km) result in a wider and more energetic MIZ, by a factor of 70% each, compared to larger floes. We hypothesize that this floe size dependency may affect sea ice break‐up by controlling oceanic energy propagation into the MIZ and modulate the sea ice pack's melt rate by regulating lateral heat transport toward the sea ice cover.